2014
DOI: 10.1089/aid.2012.0243
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: HIV Type 1 Subtype BF Leads to Faster CD4+ T Cell Loss Compared to Subtype B

Abstract: Although it has been suggested that biological differences among HIV-1 subtypes exist, their possible influence on disease progression has not been fully revealed. In particular, the increasing emergence of recombinants stresses the need to characterize disease presentation in persons infected by these diverse HIV-1 forms. We explored this issue among 83 Brazilian subjects infected with either HIV-1 subtype B or recombinant subtype BF, all followed since incident infection in a cohort study. Viral subtypes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
4
0
3
Order By: Relevance
“…The subtype distribution in our study was 53.5% CRF01_AE, 14.9% B, 27.2% CRF07_BC/CRF08_BC and 4.4% other subtypes, which was consistent with previous reports 17, 18 , indicating that recombinant forms of the virus might be on the rise worldwide, which have already been associated with faster disease progression as seen in Cuba 19 and Brazil 20 . Most importantly, our study demonstrated that CRF01_AE is associated with faster HIV/AIDS progression, which is in agreement with a previous study conducted in China 14 .…”
Section: Discussionsupporting
confidence: 92%
“…The subtype distribution in our study was 53.5% CRF01_AE, 14.9% B, 27.2% CRF07_BC/CRF08_BC and 4.4% other subtypes, which was consistent with previous reports 17, 18 , indicating that recombinant forms of the virus might be on the rise worldwide, which have already been associated with faster disease progression as seen in Cuba 19 and Brazil 20 . Most importantly, our study demonstrated that CRF01_AE is associated with faster HIV/AIDS progression, which is in agreement with a previous study conducted in China 14 .…”
Section: Discussionsupporting
confidence: 92%
“…If these new HIV-1 recombinants do spread, then they will contribute to viral diversification locally and globally and may lead to faster progression to AIDS and/or to more rapid CD4 decline than the homogenous subtypes from which they originated, as observed in, e.g., Guinea-Bissau and Brazil4748. Thus, whereas CTL responses in individuals with protective HLA-variants are beneficial for the individual, they may be detrimental to the population because they fuel HIV-1 evolution.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important factors in determining the HIV-1 genetic diversity is the identification of possible strains that are more likely to result in disease progression. Some studies in Brazil have linked BF recombinants with faster progression to AIDS-defining events [30] or faster CD4+ lymphocyte count decline [31]. Thus, the high frequency of these recombinants may be related to a greater chance of disease progression.…”
Section: Discussionmentioning
confidence: 99%